Mixed alkali-ion transport and storage in atomic-disordered honeycomb layered NaKNi2TeO6 - Titus Masese (Nature Portfolio, 2021)
Honeycomb layered oxides are an emerging class of materials with peculiar physicochemical properties. Here, the authors report the synthesis and electrochemical energy storage characterisations of a mixed-alkali honeycomb layered oxide material capable of storing Na and K ions simultaneously.